2021
DOI: 10.1126/sciadv.abh2148
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 independent of PD-L1 ligation promotes glioblastoma growth through the NFκB pathway

Abstract: PD-1 on glioblastoma cells promotes brain tumor growth, and therapeutic antibodies cannot suppress its proliferative effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Within the University of Calgary BTIC Core, these lines were cultured chronologically, preserved, and verified. Identification of the three human BTIC lines (BT048, BT53M and BT073) has been reported previously 37 .…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…Within the University of Calgary BTIC Core, these lines were cultured chronologically, preserved, and verified. Identification of the three human BTIC lines (BT048, BT53M and BT073) has been reported previously 37 .…”
Section: Methodsmentioning
confidence: 86%
“…Identification of the three human BTIC lines (BT048, BT53M and BT073) has been reported previously 37 .…”
Section: Generation Of Gbm Patient Derived Bticsmentioning
confidence: 86%
“…In contrast, non-canonical PD-1 signaling has been demonstrated in cancer cells, resulting in both protumor and tumor-suppressing effects [19]. Protumor effects of intrinsic PD-1 have been shown through multiple mechanisms including enhanced mTOR signaling and NFκB activation in some tumors and may even act indepently of PD-1/PD-L1 ligation [20][21][22][23]. On the contrary, in vitro and in vivo PDCD1 knockdown models, as well as immunodeficient mice inoculated with lung cancer cell lines and treated with anti-PD-1, showed increased colony expansion and tumor growth [15,24], mediated through upregulated AKT and ERK signaling [15].…”
Section: Discussionmentioning
confidence: 99%
“…MDR in tumors is complex and multifactorial, including biological barrier formed by the tumor microenvironment (TME) [48][49][50][51][52][53] and overexpression of drug efflux transporter resulting in the inability to accumulate drugs intracellularly [40,[54][55][56][57] , the drug inactivation due to the specific environment of gene control and metabolism, the resistance to apoptosis and deoxyribonucleic acid (DNA) damage repair [58][59][60][61][62][63] , and immune evasion [64][65][66][67][68][69][70][71] , as shown in Figure 1.…”
Section: Mechanisms Of Tumor Resistancementioning
confidence: 99%
“…Joung et al revealed that four genes, programmed death-ligand 1 (PD-L1), MCL-1, JunB proto-oncogene (JUNB), and β1,3-Nacetylglucosaminyltransferases (B3GNT2), affect the interaction of cancer cells with T cells, conferring resistance to T cell cytotoxicity [64] . Programmed cell death protein 1 (PD-1) on the T cells interacts with PD-L1 on the cancer cells to inhibit activation of T cells [67] . To address this problem, Topalian et al proposed neoadjuvant PD-(L)1 blockade therapy to enhance systemic immunity against tumors and prevent recurrence [Figure 1D] [69] .…”
Section: Immune Evasionmentioning
confidence: 99%